2021
DOI: 10.1108/ijse-02-2021-0130
|View full text |Cite
|
Sign up to set email alerts
|

Funding health in developing countries: foreign aid, FDI, or personal remittances?

Abstract: PurposeThis paper presents three models of funding health care in 130 developing countries, based upon a public system, a private system and personal remittances.Design/methodology/approachThe authors trace the funding of health from foreign aid to health funding and health outcomes in the public system, foreign direct investment to health funding in the private system, and personal remittances to health outcomes. This is followed by panel data, fixed effects models subjected to 2-, 3- and 4-stage least square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Furthermore, the FDI inflows can increase the host country's export capacity, causing the developing country to increase its foreign exchange earnings. In addition, FDI may provide a positive effect on human health by increasing the income and higher health spending; however, apart from the positive aspect of FDI, there are some negative effects associated with FDI inflow; like the abundance of FDI inflow can make the host country polluted, which will have adverse consequences on the human health of the host country's residents in terms of death rate, infant mortality, and other serious types of mortalities ( 5 ). The drawback of FDI inflow is the degradation of the air quality caused by a high level of air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the FDI inflows can increase the host country's export capacity, causing the developing country to increase its foreign exchange earnings. In addition, FDI may provide a positive effect on human health by increasing the income and higher health spending; however, apart from the positive aspect of FDI, there are some negative effects associated with FDI inflow; like the abundance of FDI inflow can make the host country polluted, which will have adverse consequences on the human health of the host country's residents in terms of death rate, infant mortality, and other serious types of mortalities ( 5 ). The drawback of FDI inflow is the degradation of the air quality caused by a high level of air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Kakhkharov et al (2021), however, finds that remittances reduce health spending in Uzbekistan, suggesting this supports the view that remittances are channeled to consumer goods. At the macro-level, some studies find that remittances increase access to health care services and private health expenditure (Abraham & Tao, 2021; Azizi, 2018; Drabo & Ebeke, 2011; Yol, 2017). However, Terrelonge (2014) finds that the effect of remittances on household health spending is insignificant, while finding that remittances improve child nutritional status.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study demonstrated that external debt worsens the welfare of SSA countries. However, Abraham and Tao ( 2021 ) conducted a study for 130 developing countries by studying the contribution of foreign health aid on life expectancy. Panel FE, 2-, 3- and 4-stage least squares techniques were employed by the study to express that foreign health aid increases life expectancy.…”
Section: Literature Reviewmentioning
confidence: 99%